A Descriptive Study of Human Salmonella Serotype Typhimurium Infections Reported in Ontario from 1990 to 1997 - Michael W Ford; Agricola Odoi; Shannon E Majowicz; Pascal Michel; Dean Middleton; Bruce Ciebin; Kathryn Doré; Scott A McEwen; Jeffery A Aramini; Shelley Deeks; Frances Jamieson; Rafiq Ahmed; et al. (Canadian Journal of Infectious Diseases)
BACKGROUND: Salmonella infections cause gastrointestinal and systemic diseases worldwide and are the leading causes of food-borne illnesses in North America (1-4). Salmonella serotype typhimurium (ST), in particular, is increasingly becoming a major public health concern because of its ability to acquire multiple resistant genes (5,6).